Grantchester [videorecording (DVD)] - Norton, James, 1985-; Green, Robson; Christie, Morven, 1979-; Runcie, James, 1959- (PBS Distribution, 2015)
It's 1953 and Sidney Chambers is vicar of Grantchester, a village just outside Cambridge, England. Sidney's is a quiet life. He tends to his flock, keeps up with his jazz collection, and does his best to contain his passion for beautiful heiress Amanda Kendall. But when one of his parishioners dies in suspicious circumstances, Sidney quickly finds that people confide things in a parish priest that they would never tell police.